Physical activity and mental health in children and adolescents with intellectual disabilities: a meta-analysis using the RE-AIM framework - Wen Yang; Xiao Liang; Cindy Hui-Ping Sit (BMC, 2022)
Abstract Background Children and adolescents with intellectual disabilities (IDs) tend to have lower levels of physical activity and poorer mental health than their typically developing peers. Studies on the effects of physical activity on the mental health of children with IDs using the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework are scarce. Methods A systematic literature review using six databases (CINAHL, Eric, PsycINFO, PubMed, SPORTDiscus, and Web of Science) was conducted from January 2000 to September 2021. Studies reporting at least one physical activity intervention and mental health outcome in children and adolescents with IDs aged between 5 and 17 years were included in the meta-analysis. Preferred Reporting Items for Systematic Review and Meta-Analysis guideline, Comprehensive Meta-Analysis, and the RE-AIM framework were utilized. Results A total of 15 studies that met the inclusion criteria were included in the meta-analysis. The effects of physical activity on mental health in children and adolescents with IDs were significant and large (Hedges' g = 0.897, p < 0.01), with medium effects on psychological health (Hedges' g = 0.542, p < 0.01) and large effects on cognitive function (Hedges' g = 1.236, p < 0.01). Randomized controlled trial (RCT) design and intervention components (> 120 minutes per week, therapeutic, and aerobic exercise) demonstrated the strongest effects. Moreover, study background (publication year, study location, and sample size), participant characteristics (age and sex), and Maintenance (RE-AIM framework) moderated the effects of physical activity on mental health. Based on the RE-AIM framework, there were higher proportions in the dimensions of Reach and Effectiveness than Adoption, Implementation, and Maintenance. Conclusions Physical activity appears to have positive effects on mental health, including psychological health and cognitive function, in children and adolescents with IDs. Physical activity interventions using the RE-AIM framework are recommended to assess short- and long-term impacts and translate scientific evidence into practice. Trial registration The protocol for this meta-analysis was registered with PROSPERO ( CRD42021256543 ).